Causal relationship between immune cells and Guillain-Barré syndrome: a Mendelian randomization study - Huaiquan Liu; Shuoshuo Shao; Bo Chen; Shili Yang; Xinyan Zhang (Frontiers in Neurology)
ObjectiveThe aim of this study was to investigate the causal effect of immune cell phenotype on GBS using two-sample Mendelian randomization (MR) approach.MethodsThis study used MR to investigate the causal relationship between 731 immune cell phenotypes and GBS. We used Inverse variance weighted, Weighted median, MR Egger, Simple mode, Weighted mode for MR analysis. We also used the Cochran Q test, MR-Egger intercept test, IVW regression and MR-PRESSO, leave-one-out analysis to assess the presence of horizontal pleiotropy, heterogeneity and stability, respectively.ResultsOur study revealed a causal relationship between 33 immune cell phenotypes and GBS. Twenty immunophenotypes were observed to be associated with GBS as risk factors. For example, CD20 on IgD+ CD38dim in the B cell group (OR = 1.313, 95%CI:1.042–1.654, p = 0.021), CD3 on CD4 Treg in Treg cell group (OR = 1.395, 95%CI:1.069–1.819, p = 0.014), CD3 on TD CD8br in Maturation stages of T cell group (OR = 1.486, 95%CI:1.025–2.154, p = 0.037), CD16 on CD14+ CD16+ monocyte in Monocyte group (OR = 1.285, 95%CI:1.018–1.621, p = 0.035), CD33dim HLA DR+ CD11b + %CD33dim HLA DR+ in Myeloid cell group (OR = 1.262, 95%CI:1.020–1.561, p = 0.032), HLA DR+ NK AC in TBNK cell group (OR = 1.568, 95%CI:1.100–2.237, p = 0.013). Thirteen immune phenotypes are associated with GBS as protective factors. For example, CD19 on PB/PC in the B cell group (OR = 0.577, 95%CI:0.370–0.902, p = 0.016), CD4 Treg AC in Treg cell group (OR = 0.727, 95%CI:0.538–0.983, p = 0.038), CD11c + monocyte %monocyte in cDC group (OR = 0.704, 95%CI:0.514–0.966, p = 0.030), CX3CR1 on CD14+ CD16− monocyte in Monocyte group (OR = 0.717, 95%CI:0.548–0.939, p = 0.016), Mo MDSC AC in Myeloid cell group (OR = 0.763, 95%CI:0.619–0.939, p = 0.011), CD45 on granulocyte in TBNK group (OR = 0.621, 95%CI:0.391–0.984, p = 0.042).ConclusionThe findings suggest that certain specific immune cell phenotypes, particularly B cell and Treg cell subpopulations, are causally associated with GBS, providing potential targets for the clinical treatment of GBS.